PENINGKATAN PEMAHAMAN SISWA DALAM MENERAPKAN SILA-SILA PANCASILA MELALUI MEDIA PEMBELAJARAN INOVATIF SD NEGERI 2 CEPIRING - Annisa Tri Hidayati; Miyanti Eka Martasari; Susilo Tri Widodo; Nur Indah Wahyuni; Agus Murdiyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was motivated by a lack of understanding of students' learning in Pancasila education subjects regarding symbols and the application of Pancasila principles in everyday life. This research aims to provide solutions to existing problems through innovative and interactive learning media in the form of Pancasila bag board and smart jellyfish learning media which involve students' activeness in critical reasoning and courage in solving a problem. The research method used in this research is classroom action research (PTK). Classroom action research is a research model in which there are four stages, namely planning, action, observation and reflection. The subjects taken in this research were all fourth grade students at SD Negeri 2 Cepiring for the 2023 academic year. The subjects in this research were 31 students consisting of 11 boys and 20 girls. The instruments (data collection tools) used were interviews, documentation, observations, question items, and student report card learning results in the Pancasila Education subject. Based on the results of the research that has been carried out, it can be seen that there is an increase in student learning outcomes in pre-cycle activities, 15 students got a score of 60-70, 9 students got a score of 71-80, 6 students got a score of 81-90, and only 1 student got a score of 91-100. . In the first cycle, the learning outcomes obtained were 2 students with scores of 40-60, 9 students with scores of 60-80, and 17 students with scores of 90-100. And in cycle II, the learning outcomes obtained were 2 students with scores of 40-60, 7 students with scores of 60-80, and 19 students with scores of 90-100. Therefore, using this learning media can improve students' understanding of learning in Pancasila education subjects in the material on the application of Pancasila principles in class IV of SD Negeri 2 Cepiring, Cepiring District, Kendal Regency in the 2023/2024 academic year.